(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2023)
The retail industry has been affected by advanced technology: Different channels have been connected to offer a seamless customer experience, leading to a shift from a multichannel to an omnichannel strategy. Both academia and industry have focused on this phenomenon in order to serve customers effectively. This study aims to explore the impact of omnichannel capability, customer service, and value on customer experience. In order to collect data, an online survey was administered to consumers who have experience buying from retailers via online and physical stores. To test the research hypotheses, structural equation modeling (SEM) was employed. Our findings indicate that customer service and value have a direct and significant impact on customer experience. Furthermore, it is found that omnichannel capability plays no significant role in customer experience.